Analysis of Salicylic Acid in Biological Fluids (Serosal) Using Uv-Vis Spectrophotometry - Chintia D; Resca S.S.; Anggra I.N.A (Universitas STRADA Indonesia, 2024)
Pharmacokinetics is an aspect of pharmacology that covers the fate of drugs in the body, namely absorption, distribution, metabolism, and excretion (ADME). Overall, bioavailability shows the kinetics and comparison of the levels of active substances that reach the bloodstream to the amount of drug given. Method validation is carried out to determine that the analytical method used is accurate, specific, reproducible, and resistant to the analyte to be analyzed. An analysis model must be validated to verify that its performance parameters are sufficient to overcome the analysis problem. The research method used is included in observational experimental research. Observational experimental research is research conducted by analyzing a compound and testing it. The results of this study obtained a standard curve value of Y = 0.006x + 3.401, r2 = 0.334 with λmax 329 nm. Recovery (% recovery) in the study, the average recovery value of the concentration was 200μg/mL (118.8%); 150 μg/mL (72.1%); 100 μg/mL (131.5%). Systemic error of series concentration 200 μg/mL (-18.8%); 150 μg/mL (278%); 100 μg/mL (-31.5%). Based on the study, validation testing of the method with further precision and accuracy is needed.